Diagnostic Accuracy of Chest X-Ray in Detecting Chest Tube Malpositions - Nargis Maqbool, Farhan Zaheer, Mohammad Taha Kamal, Shehzadi Rimsha, Fizza Iftikhar, Bushra Shakeel, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the diagnostic accuracy of chest x-ray in detecting chest tube malpositions. Design of the Study: It was a cross-sectional survey. Place and Duration of Study: This study was carried at the Department of Radiology, Civil Hospital Karachi and Shaheed Mohtarma Benazir Bhutto (SMBB) Trauma Centre Karachi over 6 months from28th January 2021 to 27th July 2021. Patients and Methods: This study comprised a total of 191 patients with blunt or penetrating chest damage needing a tube thoracotomy. An incision in the skin was made directly above the rib. A suitable-sized chest tube was placed inside, fastened with a silk 1-0 suture, and an aseptic dressing was placed. The patient was subsequently transported for a chest CT scan without contrast and a X-ray of chest (frontal and lateral views). Chest tube malposition, or CTM, was identified on a frontal, lateral, or both radiographs. All information was recorded in the Performa. Results: The patients were 35.9611.387 years old on average. 26.1% (52/199) of the patients had malposition, which was verified by CT. The frontal chest x-sensitivity, ray's specificity, positive predictive value, negative predictive value, and accuracy in detecting malposition were 36.5%, 100%, 100%, 81.7%, and 83.4%, respectively, and the lateral chest x-were ray's 15.4%, 100%, 100%, 77%, and 77.9%%. The combined frontal and lateral chest x-sensitivity, ray's specificity, PPV, NPV, and accuracy were 38.5%, 100%, 100%, 82.1%, and 77.4%, respectively, in detecting malposition. 83.4% of chest x-rays with combined frontal and lateral views correctly identified malposition. Practical Implication: A literature search reveals that there is relatively little information available about this topic in our population. As a result, it gives the study a solid justification since its main objective is to compare the diagnostic efficacy of frontal and lateral CXR to that of a CT scan in identifying chest tube malposition. Conclusion: When a chest x-ray is taken from both the front and the side, its accuracy in detecting malposition is 83.4 percent. In high negative and positive findings for the diagnosis of thorax injuries make chest X-ray an essential aspect of the first therapy of a trauma patient. Keywords: Diagnostic Accuracy, Thoracostomy, Chest tube malpositions, Chest X-Ray, CT scan, Radiology